1986
DOI: 10.1152/ajpgi.1986.251.1.g64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atropine on rat pancreatic secretory response to trypsin inhibitors and protein

Abstract: The effect of atropine on the exocrine pancreatic secretory response to intestinally infused trypsin inhibitor and protein in conscious rats was investigated. Bile and pancreatic juice were collected and continuously returned to the intestine throughout all experiments. Ovomucoid trypsin inhibitor (OMTI) was infused at 1, 3, 6, 12, and 30 mg/h id, simultaneously with intravenously infused atropine (100 micrograms X kg-1 X h-1) or 0.15 M NaCl. Casein was infused at 300 mg/h id with or without intravenous atropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…MK-329 abolished and atropine had no significant effect on protein or fluid secretion stimulated by 62.5 pmol⅐kg Ϫ1 ⅐h Ϫ1 of CCK-58 (not shown). The absence of inhibitory effects of atropine on pancreatic secretion stimulated by exogenous or endogenous cholecystokinin in conscious, recovered rats is well established (6,33,41). Surprisingly, MK-329 had no effect on the pancreatic fluid secretion caused by 500 pmol⅐kg Ϫ1 ⅐h Ϫ1 of CCK-8, while abolishing protein output (not shown).…”
Section: Role Of Cck-a Receptor Cholinergic Pathways and Secretin Imentioning
confidence: 80%
“…MK-329 abolished and atropine had no significant effect on protein or fluid secretion stimulated by 62.5 pmol⅐kg Ϫ1 ⅐h Ϫ1 of CCK-58 (not shown). The absence of inhibitory effects of atropine on pancreatic secretion stimulated by exogenous or endogenous cholecystokinin in conscious, recovered rats is well established (6,33,41). Surprisingly, MK-329 had no effect on the pancreatic fluid secretion caused by 500 pmol⅐kg Ϫ1 ⅐h Ϫ1 of CCK-8, while abolishing protein output (not shown).…”
Section: Role Of Cck-a Receptor Cholinergic Pathways and Secretin Imentioning
confidence: 80%
“…The effect of atropine on feedback regulation of pancreatic secretion however is controversial. Other investigators showed that atropine has no effect in conscious rats (28). Experimental design may account for these differences.…”
Section: Discussionmentioning
confidence: 96%
“…The vagus nervous system has been assumed to be another factor that regulates pancreatic secretion, and the inhibition of the cholinergic nerve system reduces pancreatic secretion (7). It has been reported that the quantity of atropine used in this experiment is sufficient to inhibit pancreatic secretion (16). Despite the intravenous administration of this quantity of atropine, however, platycodin D started to stimulate pancreatic secretion 30 mm after administration (Fig.…”
Section: Discussionmentioning
confidence: 63%